ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI PADANG (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2015)
This study aimed to analyze and see the influence of factors influencing students’ achievement of Economical Faculty of Padang State University. This study was explorative study. The population was all of students majoring in S1 Economical Faculty of Padang State University; the total was 1546 students. In taking the sample, it was used the proportional random sampling with the total sample was 318 students. The data were analyzed by using descriptive analysis, factorial analysis, and regression analysis and the hypothesis was analyzed by using T-test. The result showed that (1) there were eight factors influence the students’ achievement such as (a) teaching quality factors included lecturers’ creativity, lecturers’ understanding, facilities, learning references, and learning atmosphere in campus; (b) independency factors included competitive atmosphere, taking initiative, teamwork, and study preparation; (c) internal condition factors included living atmosphere, family relationship, and parents’ attention; (d) ethic factors included learning motivation, learning effort, and ability to solve the problems; (e) concentration variables included physic condition, tiredness, and learning variables; (f) eating habit and achievement factors include eating and achievement to be succeed; (g) supplement factors included learning atmosphere, financial condition and participation in learning; (h) caring factors include how the parents treated the children. (2) the regression showed that the eating habit, achievement to be succeed and caring variables were not significantly influence toward students achievement. Key Word : Internal factor, external factor and learning achievement